Comparative Analysis of Traditional and Molecular Methods for Detecting Human Papillomavirus in Histology and Cytology Samples - ALMUTIRI, ABDULLAH (Journal of Biological Insights, 2026)
Abstract Human Papillomavirus (HPV) is a critical factor in the pathology of various carcinomas, including cervical cancer, and warrants improved testing platforms for effective management and therapeutic outcomes. This study aims to comparatively evaluate the various traditional methods and molecular diagnostic platforms that are deployed in the screening for HPV in histological and cytological samples. In this study, we systematically x-rayed the strengths and limitations of various diagnostic tools utilized in cervical cancer screening, including the Pap smear, histopathological examination, Polymerase Chain Reaction (PCR), In Situ Hybridization (ISH), Immunohistochemistry (IHC), and Next-Generation Sequencing (NGS), with view to provide a comprehensive exposition of their utility. The strengths of various molecular methods deployed in detecting high-risk HPV genotypes and their localized viral presence, as well as the augmented efficiency obtainable by integrating various diagnostics techniques. Ultimately, this study seeks to establish a robust framework for the selection and application of HPV detection methods to enhance clinical decision-making and improve patient outcomes in HPV-related disease management. Keywords: Human Papillomavirus, Polymerase Chain Reaction, In Situ Hybridization, Immunohistochemistry, Next-Generation Sequencing. الملخص يُعدّ فيروس الورم الحليمي البشري (HPV) عاملاً محورياً في مسببات العديد من الأورام الخبيثة، بما في ذلك سرطان عنق الرحم، مما يبرز الحاجة إلى تطوير اختبارات فحص أكثر دقة لتحسين التشخيص والعلاج والنتائج السريرية. تهدف هذه الدراسة إلى إجراء تقييم مقارن بين الطرق التقليدية والتحاليل الجزيئية المستخدمة في الكشف عن فيروس الورم الحليمي البشري في العينات النسيجية والخلوية. وقد قمنا في هذا الاستعراض بتحليل منهجي لنقاط القوة والضعف في أبرز الأدوات التشخيصية المستخدمة في برامج الكشف عن سرطان عنق الرحم، بما في ذلك اختبار بابانيكولاو (Pap smear)، والفحص النسيجي المرضي، وتفاعل البوليميراز المتسلسل (PCR)، والتهجين الموضعي (ISH)، والكيمياء المناعية النسيجية (IHC)، وتسلسل الجيل التالي (NGS)، مع التركيز على مدى كفاءتها وفائدتها التشخيصية. كما يستعرض هذا العمل المزايا التي توفرها الطرق الجزيئية المختلفة في الكشف عن الأنماط الجينية عالية الخطورة من الفيروس وتحديد توضعه في الأنسجة، إضافةً إلى الكفاءة التشخيصية المعززة الناتجة عن دمج أكثر من تقنية واحدة. وفي النهاية، تسعى هذه الدراسة إلى وضع إطار علمي متين لاختيار وتطبيق طرق الكشف عن فيروس الورم الحليمي البشري بما يدعم اتخاذ القرار السريري ويحسّن نتائج المرضى في إدارة الأمراض المرتبطة بهذا الفيروس. الكلمات المفتاحية: فيروس الورم الحليمي البشري، تفاعل البوليميراز المتسلسل، التهجين الموضعي، الكيمياء المناعية النسيجية، تسلسل الجيل التالي.